Determination of the Chemical Oxygen Demand Using a Cu‐Au Anisotropic Nanoalloy‐Modified Screen‐Printed Electrode: A Sustainable and Sensitive Solution - Federica Simonetti; Francesca Polli; Roberta Di Costanzo; Leonardo Nichele; Giulia Simonetti; Jang‐Yeon Hwang; Marco Agostini; Franco Mazzei; Rosaceleste Zumpano (ChemElectroChem)
This study presents a new, non‐enzymatic electrochemical sensor based on gold‐copper nanobrambles (Au‐CuONBs) for rapid and accurate chemical oxygen demand (COD) monitoring in water. COD, an essential metric of water quality, is typically assessed using labor‐intensive methods with high toxicity and limited tolerance to chloride interference. The Au‐CuONBs‐based sensor here proposed overcomes these limitations by offering high sensitivity, a broad linear detection range (0.1–10.3 mM glucose), and robust tolerance to chloride ions, enabling accurate measurements even in challenging water samples. Tested on real wastewater samples, the sensor delivered results closely aligned with standard COD methods, with a detection limit of 11 μM and response time of only 5 min. This portable, cost‐effective sensor provides a promising solution for sustainable on‐site COD analysis, enhancing water quality management and environmental monitoring.